Fostering university students’ autonomous motivation through a societal impact project: a qualitative study of students’ and teachers’ perspectives - Yuanyuan Zhu; Latifa Abidi; Hans Savelberg; S. Eleonore Köhler; Rashmi A. Kusurkar; Diana Dolmans (BMC Medical Education)
Abstract Background Fostering students’ autonomous motivation is linked to numerous positive outcomes. However, stimulating autonomous motivation of students in health professions remains a challenge. According to the Self-Determination Theory, supporting students’ basic psychological needs for autonomy, relatedness, and competence fosters their autonomous motivation. However, there is a lack of studies that explore how and why education might enhance students’ autonomous motivation. We designed, implemented, and investigated an extracurricular project called the ‘Societal Impact Project’ (SIP) to support students’ basic psychological needs and autonomous motivation through three principles, offering authentic and collaborative learning experiences as well as scaffolding. This study aimed to understand how and why the SIP with characteristics of authentic and collaborative learning, and scaffolding supports students’ autonomy, relatedness, competence, and autonomous motivation from the students’ and teachers’ perspectives. Methods First-year students following the bachelor programmes of Biomedical Sciences and Health Sciences participated in the project. Students and teachers took part in focus groups conducted after the project. We adopted thematic analysis. Results Students reported that, firstly, having freedom was motivating, but students needed different adaptive degrees of guidance throughout the project. Secondly, working in small groups could be motivating or demotivating, but having peer connections and openly discussing difficulties made the groups strong. Thirdly, societal relevant problems stimulated motivation and learning as students recognized the real-life value of the problems, but the relevance of these problems to students’ curriculum was not always clear to them. Conclusions SIP reflected characteristics of the three educational principles, and students reported that these elements contributed to student’s basic psychological needs and autonomous motivation. A careful balance is needed in terms of offering autonomy versus support. Furthermore, students faced difficulties in seeing the link between the societal relevant problems and their curricula.